Caribbean discourse in inclusive education. book 1 : historical and contemporary issues - Conrad, Dennis Michael, 1949-; Blackman, Stacey (Caribbean discourse in inclusive education (Series) ;, 2017)
Caribbean Discourse in Inclusive Education is an edited book series that aims to give voice to Caribbean scholars, practitioners, and other professionals working in diverse classrooms. The book series is intended to provide an ongoing forum for Caribbean researchers, practitioners, and academics, including those of the Diaspora, to critically examine issues that influence the education of children within inclusive settings. The book series is visionary, timely, authoritative and presents pioneering work in the area of inclusive education in the Caribbean, as part of the broader South-South dialogue. It is essential reading for students in undergraduate and postgraduate programmes, scholars, teachers, researchers and policy makers at the regional and international level. The first book in this series entitled Historical and Contemporary Issues will trace the history and examine the Caribbean's trajectory towards the development of inclusive education in the 21st Century. The main premise of the book is that inclusion remains an ideologically sound goal, which remains elusive in the Caribbean. It will also provide a wider platform to discuss other factors that influence the development of inclusive education such as school climate, culture and ethos, LGBT issues, teacher training and professional development, pedagogy, pupil perspective, curriculum, policy and legislation.